2023
DOI: 10.1039/d2sc04926k
|View full text |Cite
|
Sign up to set email alerts
|

The kinked structure and interchain van der Waals interaction of carbyne nanocrystals

Abstract: Carbyne with the one-dimensional sp-hybridized carbon atoms is the third form of carbon following diamond and graphite. Although carbyne nanocrystals have been synthesized, little is known about its structural details....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“… 29 Also, Cao et al recently reported the experimental evidence for the formation of kinked carbon chains and interchain van der Waals interactions in carbyne nanocrystals. 30 Intriguingly, Chalifoux et al described the synthesis of the longest series of conjugated polyynes as a potential model for determining the sp-hybridized carbon atoms in a linear fashion. 25,31 On the other hand, by using the most familiar graphene layers or CNTs as the sp 2 hybridized templates, numerous attempts have been made to control the formation of linear sp-hybridized carbyne chains within the nanostructured sp 2 matrices in the presence or absence of metal supports.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Also, Cao et al recently reported the experimental evidence for the formation of kinked carbon chains and interchain van der Waals interactions in carbyne nanocrystals. 30 Intriguingly, Chalifoux et al described the synthesis of the longest series of conjugated polyynes as a potential model for determining the sp-hybridized carbon atoms in a linear fashion. 25,31 On the other hand, by using the most familiar graphene layers or CNTs as the sp 2 hybridized templates, numerous attempts have been made to control the formation of linear sp-hybridized carbyne chains within the nanostructured sp 2 matrices in the presence or absence of metal supports.…”
Section: Introductionmentioning
confidence: 99%